Correlation between antenatal care (ANC) visits and caffeine beverage consumption habits with the incidence of anemia in third trimester pregnant women in Health Centers, Bantul Region - Anggi Widiyanti; Fatimah Fatimah; Muafiqoh Dwiarini (Alma Ata University Press, 2024)
mother and baby.  Efforts made by health workers to reduce the occurrence of anemia by conducting Antenatal Care (ANC) visits, and providing Communication, Information, and Motivation (KIM) and administering Fe tablets.  Consumption of Fe tablets is better consumed using plain water because if Fe tablets are taken together with tea and coffee it can inhibit iron absorption. Objectives: Determine the relationship between Antenatal Care (ANC) visits and consumption habits of caffeinated drinks with the incidence of anemia in third trimester pregnant women at the Health Center in Bantul. Methods: This type of research uses quantitative research with a cross sectional approach.  Sampling using simple random sampling and quota sampling with the number of respondents 180 pregnant women using predetermined characteristics.  The research instrument used a questionnaire on the variable ANC visits and consumption habits of caffeinated drinks and used the KIA handbook on the variable incidence of anemia in pregnant women. The bivariate analysis technique uses the Kendal Tau test. Results: In the ANC visit variable, a p value = 0.029 (p <0.05) was obtained, indicating that there is a relationship between Antenatal Care (ANC) visits and the incidence of anemia in third trimester pregnant women.  In the habitual variable of caffeine consumption, the p-value = 0.004 (p <0.05), indicating that there is a relationship between the habit of consuming caffeinated drinks and the incidence of anemia in third trimester pregnant women. Conclusions : There is a relationship between Antenatal Care (ANC) visits and the incidence of anemia and there is a relationship between the habit of consuming caffeinated drinks and the incidence of anemia in third trimester pregnant women at the Health Center in Bantul.